2004
DOI: 10.2991/jnmp.2004.11.3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Quantum Field Fluctuations on Chaotic Dynamics of Yang-Mills System II. The Role of the Centrifugal Term

Abstract: We have considered SU (2) U (1) gauge field theory describing electroweak interactions. We have demonstrated that centrifugal term in model Hamiltonian increases the region of regular dynamics of Yang-Mills and Higgs fields system at low densities of energy. Also we have found analytically the approximate relation for critical density of energy of the order to chaos transition on centrifugal constant M. It is necessary to note that mentioned increase of the region of regular dynamics has linear dependance on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…It was also observed that if the ratio of coupling constants of Yang-Mills and Higgs fields is larger than some critical value, quantum corrections do not affect the chaotic dynamics of Yang-Mills and Higgs fields. It was demonstrated that centrifugal term in the model Hamiltonian increases the region of regular dynamics of Yang-Mills and Higgs fields system at low densities of energy [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that if the ratio of coupling constants of Yang-Mills and Higgs fields is larger than some critical value, quantum corrections do not affect the chaotic dynamics of Yang-Mills and Higgs fields. It was demonstrated that centrifugal term in the model Hamiltonian increases the region of regular dynamics of Yang-Mills and Higgs fields system at low densities of energy [8].…”
Section: Introductionmentioning
confidence: 99%